Epilepsy in Colombia: Epidemiologic profile and classification of epileptic seizures and syndromes (2006)
Purpose: A national study was performed in Colombia to determine the general and regional prevalence of epilepsy, clinical profiles, seizure types, and clinical syndromes. Methods: Based on the National Epidemiological Study of Neurological Diseases (EPINEURO), we evaluated and followed up for 1 year all the subjects with epilepsy from the National Sample. Clinical profiles were further assessed. Seizure types and epilepsy syndromes were established according to the international classifications. Results: General prevalence was found to be 11.3 per 1,000, with little variation among regions, except the eastern region, where prevalence was 23 per 1,000; prevalence for active epilepsy was 10.1 per 1,000. Women have a slightly greater (not statistically significant) risk. Most seizures are focal (partial), frequently with secondary generalization. The most frequent epilepsy syndrome encountered was partial symptomatic/cryptogenic (80%). Epilepsy onset in Colombia occurs most frequently in childhood. Conclusions: Prevalence rates of epilepsy in Colombia are similar to those reported in nations with comparable developmental status and have diminished over time. The study presents the distribution of seizures and syndromes. The most frequent types are focal syndromes. © 2006 International League Against Epilepsy.